Survival of the fittest: survival and longevity among male Australian elite athletes - Lystad, R. (Journal of Science and Medicine in Sport, 2024)
Introduction: Elite athletes typically outlive the general population by 4-7 years due to lower risk of cardiovascular disease and cancer mortality. Although there are growing concerns about neurodegenerative disease in contact sports, it is generally taken for granted that "benefits outweigh harms" in terms of survival and longevity. This study aimed to quantify and compare survival and longevity in three populations of male Australian elite athletes, relative to sex- and age-matched referents from the general population. Methods: This retrospective cohort study comprised a census of three populations of male Australian elite athletes (i.e. N=10,502 Australian Football League [AFL] players, N=803 national team rugby union [Wallaby] players, and N=1,527 Olympic athletes) who debuted from 1 January 1921 to 31 December 2023. The cohorts were identified by compiling and cross-referencing information from open online sources, and Australian general population life tables were obtained from the Human Mortality Database. Survival time was calculated from the date of debut until the date of death, end of the follow-up period (i.e. 31 December 2023), or censoring date, whichever came first. Athletes were censored at age 90 years to avoid issues with high variability due to data sparsity at very old ages. Nonparametric relative survival analysis was conducted using the Kaplan-Meier estimator to generate survival curves, the Pohar Perme method and a log-rank type test to estimate and compare net survival, and the life years difference measure to estimate longevity gains or losses. Results: The median age at death was 75.7 (IQR 64.7-83.9) years for AFL players, 74.5 (IQR 64.0-82.1) years for Wallaby players, and 78.1 (IQR 64.3-86.0) years for Olympic athletes. AFL and Wallaby players initially had modest gains in life years that peaked at 56.3 and 47.6 years post-debut, at which times the average life years difference were 0.74 (95%CI 0.53 to 0.95) and 0.35 (95%CI -0.27 to 0.98) years, respectively. Subsequently, both AFL and Wallaby players exhibited a gradual decline in life years difference, with the average life years difference being 0.31 (95%CI -0.03 to 0.65) and -0.77 (95%CI -1.98 to 0.44) years at maximum follow-up time, respectively. Olympic athletes had a continuous gain in life years throughout the entire follow-up period, with the average life years difference being 3.40 (95%CI 2.29 to 4.51) years at maximum follow-up time. The log-rank type test revealed a significant difference in net survival between the three cohorts (test statistic=22.2; df=2; p<0.001). Discussion: The expected survival benefit usually observed among elite athletes was preserved in Olympic athletes, but not in AFL and Wallaby players, who exhibited a decline in relative survival from about 70 years of age. These findings are consistent with the notion of increased risk of neurodegenerative disease in contact sport athletes exposed to repetitive head trauma; however, further research examining cause-specific mortality is warranted to elucidate the underlying reasons for the observed decline in relative survival in AFL and Wallaby players. Impact/Application to the field: These findings challenge the traditional dogma that the "benefits outweigh harms" in terms of survival and longevity among Australian contact sport athletes. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.